Back to the void - Gabriel Gatti; Jaume Peris; Iñaki Robles Elong; Silvia Rodríguez Maeso; Ramón Sáez Valcárcel (Oñati Socio-Legal Series)
Absence is a common topic in the literature that analyzes forced disappearances and the disappeared. This is understandable because approaches from this concept have brought about remarkable insights. However, as it usually happens when something is naturalized, the concept’s content and its derivations have lost centrality and we find it hard to tell what’s the meaning of this concept. In an endeavor to develop a rigorous definition of ‘social disappearance’, this article looks back at the concept, focuses on its dominant uses and, above all, searches for ways to fill it with content. The present work moves forward with the renovation of this notion.